Urgensi Perluasan Objek Praperadilan Dalam Tindak Pidana Korupsi Ditinjau Dari Perspektif Perlindungan Hak Asasi Tersangka - Ardli Nuur Ihsani (Legal Standing : Jurnal Ilmu Hukum, 2017)
This present study aims to explore the urgency of pretrial object expansion as the Constitutional Court decision No21/PUU-XII/2014 on the criminal act of corruption is issued and this decision’s suitability with the objectives of pretrial concept. This research design of this study is normative research in which it used primary and secondary sources of law as the subject of study. Moreover, these sources are analyzed by using syllogism of deductive reasoning. Based on the analysis, it can be concluded that Constitutional Court Decision No 21/PUU-XII/2014 is claimed to be significant as it is viewed from the perspective of suspects’ human rights. However, in the criminal act of corruption field, this expansion of pretrial object limits the Corruption Eradication Commission in eradicating the corruption acts and results the legal uncertainty because in fact, verdicts regarding the pretrial proposal are different among each other. Besides, they could not provide the legal certainty on what case is exactly questioned in pretrial object. This is due to the high number of pretrial proposal made by the suspects by claiming that the investigator team who conduct the investigation is not authorized to do so instead of claiming of the completion of prior evidence.